(untitled) (Bangladesh Journal of Agricultural Research, 2013)
The Imidacloprid insecticide, Gaucho 70 WS at 1.5, 2.5, 3.5, 4.5 and 5.5 g/kg seed was used as seed treatment and monocrotophos 40 WSC at 1120 ml/ha was applied as foliar spray on CB9 cotton cultivar to suppress aphid, whitefly and thrips, and impact on their natural enemies during 2008-2011 at the Regional Cotton Research Station, Dinajpur, Bangladesh. The activity of natural enemies, such as ladybird beetle, lacewing, syrphid, and spider population on the sucking pests attacking cotton cultivar CB9 and yield of cotton were recorded. Imidacloprid significantly reduced aphid, whitefly, and thrips population on cotton crops compared to untreated control or foliar spray of monocrotophos 40 WSC at 1120 ml/ha. Ladybird beetles, lacewings, syrphids, and spiders were abundant in the field but their population decreased in the treated plots compared to untreated control. The CB9 cotton cultivar produced significantly higher yield (1.73 t/ha) with a benefit cost ratio 12.47 when seeds were treated with Imidacloprid at 5.5 g/kg fuzzy seed. This study indicated that Imidacloprid (Gaucho 70 WS) used as a seed treatment may be suggested to the cotton growers for controlling sucking pests. Bangladesh J. Agril. Res. 38(1): 61-70, March 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i1.15190